The Impact of a Training Program Using Brain-based Learning Theory in the Development of Creative Thinking and Skills of Passing and Scoring of Young Player's Handball - Nabeel. Kazem Heribd (Journal of Global Pharma Technology, 2018)
Through field work and handball experience it was noted that there are weaknesses in the performance of basic skills (passing and scoring) and correct behavior and lack of appropriate solutions for players to perform basic skills and this negatively affects the performance of the player and thus the results of the team believes one of these reasons weakness in the creative thinking of players Therefore, the researcher sought to use the theory of learning based on the brain in the development of creative thinking and skills of passing and scoring of young players handball.This experiment is the first step in the sport in general and in the field of handball in particular, and the objectives of the research:Preparation of a training program using the theory of learning based on the brain to develop creative thinking and skills of passing and scoring of youth handball in the club Alqasim Sports.To identify creative thinking and skills of passing and scoring of youth handball in the club Alqasim Sports.Knowledge of the impact of the training program using the theory of learning based on the brain to develop creative thinking and skills of passing and scoring of youth handball in the club Alqasim Sports.The researcher used the experimental method and determined the research society of the players of the club Alqasim youth of handball, the number of (19) players were drawn random sample of the number (12) and were divided into two groups (control and experimental) The most important conclusions are:The training program using brain-based learning theory has a positive impact on the development of creative thinking of young players in handball.The approach adopted by the coach has a positive impact in the development of skills of passing and scoring of young player's handball.The training program using brain-based learning theory has a better effect on the development of the skills of passing and scoring of young player's in handball.Keywords: Training program, Brain, Learning theory, Creative thinking and handball.